German brakes on integration: Consequences and dangers of the Federal Constitutional Court judgment for Germany and the EU - Peter Becker; Andreas Maurer (Stiftung Wissenschaft und Politik (SWP), 2009)
In its judgment of 30 June 2009, the German Federal Constitutional Court (Bundesverfassungsgericht), based in Karlsruhe, coupled its endorsement of the Treaty of Lisbon with the demand that the rights of the Bundestag and Bundesrat to participate in the further development of the European integration process be strengthened. According to the Court, any simplified procedure for amending or adapting the Lisbon Treaty requires a statutory provision governing the rights of participation. The Court used its judgment to fundamentally redefine the existing political and legal boundaries of the European integration process in Germany, by specifying the areas in which the national legislature has inviolable sovereignty of action. In so doing, the Court limits the responsibility of the Bundestag and Bundesrat on European integration policy to monitoring the European policy decisions of the executive and places the focus of parliamentary involvement in European policy on taking qualitative steps of integration
Keywords: 320